2018
DOI: 10.1016/j.ijdrr.2018.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Household construction knowledge acquisition in post-disaster shelter training

Abstract: The incorporation of safer building practices into shelter after disasters continues to plague recovery efforts. While limited resources are one potential cause, evidence from case studies suggests that poor adoption of safer construction may stem from a knowledge deficit. Despite these shortcomings, previous research has done little to examine the current state of construction education and training in post-disaster shelter and housing, and there is lacking evidence to support how households acquire new knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Several studies have demonstrated the significance of the role of knowledge, both local and scientific, to increase resilience in the face of disasters (Fujieda & Kobayashi 2013 ; Oktari et al 2015 , 2018 ). The process of how knowledge about risks is obtained and disseminated is also an introductory note for efforts to increase disaster resilience (Haruyuma & Taresawa 2014 ; Ikeda, Narama & Gyalson 2016 ; Opdyke, Javernick-Will & Koschmann 2018 ). Therefore, this KCCR framework is intended to provide input for the governments and practitioners in making efforts to increase community resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the significance of the role of knowledge, both local and scientific, to increase resilience in the face of disasters (Fujieda & Kobayashi 2013 ; Oktari et al 2015 , 2018 ). The process of how knowledge about risks is obtained and disseminated is also an introductory note for efforts to increase disaster resilience (Haruyuma & Taresawa 2014 ; Ikeda, Narama & Gyalson 2016 ; Opdyke, Javernick-Will & Koschmann 2018 ). Therefore, this KCCR framework is intended to provide input for the governments and practitioners in making efforts to increase community resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers, however, examined the crucial success aspects of home rebuilding projects during the pre-construction phase (Sospeter et al, 2020). Others emphasised the difficulties of efficient resource management (Chang et al, 2010) and the roles of guidelines (Ahmed, 2011), participatory planning (Davidson et al, 2007;Ganapati & Ganapati, 2009;Kitzbichler, 2011;Tauber, 2015), cooperation among participants (Rahmayati, 2016), governance (Guarnacci, 2012), and construction training (Opdyke et al, 2018) in the permanent housing reconstruction process, as well as proposed practice measures for managing permanent housing reconstruction.…”
Section: Post-disaster Housing Reconstructionmentioning
confidence: 99%
“…Individuals and households need knowledge to address recovery concerns and knowledge is contingent on access to information (at least in significant part). They often require information about reentry (Lin et al 2014), post-disaster assistance sources and how to access them (Longstaff 2005;Pleissis et al 2015;Rivera 2017;Chandrasekhar et al 2018), how to complete recovery tasks (Opdyke et al 2018), and opportunities to engage in wider community recovery planning efforts (Denters and Klok 2010). It appears that the more connected IHs are to sources of information central to response and recovery pre-disaster, the more ready they are to access needed information and act in keeping with it; yet, scholars have not historically assessed information source integration when researching IHP.…”
Section: The Holistic Individual Preparedness Modelmentioning
confidence: 99%